Reframing Teach For America: A conceptual framework for the next generation of scholarship - Janelle Scott; Tina Trujillo; Marialena D. Rivera (Arizona State University, 2016)
In this article, we advance a conceptual framework for the study of Teach For America (TFA) as a political and social movement with implicit and explicit ideological and political underpinnings. We argue that the second branch of TFA's mission statement, which maintains that TFA's greatest point of influence in public education is not in classrooms, but in its facilitation of entry into leadership positions aimed at reshaping public schooling, can be better understood in terms of the organization's: a) infusion of "policy entrepreneurs" into educational policymaking processes; b) cultivation of powerful networks of elite interests; c) promotion of "corporate" models of managerial leadership; and, d) racial and social class identities of its corps members that facilitate entry into leadership and policy networks. Our framework is informed by the extant research literature on TFA, interview data from more than 150 alumni and corps members, and our observations of TFA's 20th Anniversary Summit in Washington, D.C., as an illustrative case of TFA's messaging and general orientation toward educational reform. We conclude that this framework can help illuminate under-examined political and ideological motivations behind the organization's activities.